Diagnosis Gangguan pada Sistem Transmisi Daya Listrik Menggunakan Metode Pengukuran Untuk Area Yang Luas - Herman Syaibi; Azriyenni Azhari Zakri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This research has proposed a wide area measurement method used for the fault diagnosis of a short circuit in the electric power transmission system that combining the functions of a phasor measurement device. Phasor Measurement Unit (PMU) is a technology that makes Electric Power Systems has synchronous phasor measurement devices that are continuously updated of real-time. The PMU provides a measurement of the current phasor value and voltage phasor value to the control centere. Therefore, in this study measurement method model is designed to measure the wide area to using PMU on the IEEE 9-Bus System by Matlab/Simulink R2016a. The short circuit simulation is operated with variation of location each transmission line in the IEEE 9-Bus System. The results of wide area measurement method using PMU produce a diagnosis of fault. The achieved results by determining the fault location point through diagnosis of fault location with calculation highest percentage error is 0,481208%.Keywords: fault diagnosis, PMU, short circuit, transmission line, wide area.